Direct observations of negative ions on the Lunar surface by Chang'E-6 - Martin Wieser; Aibing Zhang; Romain Canu-Blot; Wengjing Wang; Gabriella Stenberg Wieser; Lianghai Xie; Stas Barabash; Tianhua Zhong; Xiao-Dong Wang; Yongliao Zou; Máté Kerényi; Weibin Wen; et al. (Communications Earth & Environment)
Abstract The solar wind can interact directly with the surface of airless bodies like the Moon. The interaction causes sputtering of surface materials and solar wind ions are also partially backscattered to space. Particles leaving the surface can have any charge-state. At the Moon, backscattered or sputtered positive ions1–4 and energetic neutral atoms5–8 have been observed, but all attempts to find negative ions in electron measurements have failed so far. Here we present measurements by Chang’E-6 from the lunar farside9 revealing the existence of a layer of negative ions close to the lunar surface. We found that about $$2.{5}_{-0.8}^{+1.2} %$$ 2 . 5 − 0.8 + 1.2 % of the impinging solar wind protons charge exchange on the lunar regolith and are backscattered as negative hydrogen ions. The negative ion fraction is similar to the observed positive ion fraction1,3. We estimate a H− surface density of $$0.1{8}_{-0.03}^{+0.04}\,{{{{\rm{cm}}}}}^{-3}$$ 0.1 8 − 0.03 + 0.04 cm − 3 . On the dayside, the lifetime of negative hydrogen ions is short due to photodetachment10, confining them to a layer with a scale height of about 10 km. Such surface-bound layers or regions with negative ions should exist at any planetary object with a surface directly exposed to solar wind11,12, including low gravity bodies such as asteroids or comets.